Development of Learning Media to Improve Students' Higher Order Thinking Skills in Circular Motion Material - Zulhelmi Zulhelmi; Naila Fauza; Dina Syaflita; Juli Pratiwi; Tommy Tanu Wijaya; Neni Hermita (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this research is to develop learning media that can improve students' Higher Order Thinking Skills (HOTS) on the topic "circular motion". Therefore, its design is a research and development (R&D) study with 4D model (Define, Design, Develop, and Disseminate). Experts were involved to validate the products that had been developed, which are teaching props and Student Worksheets (SWS), through a validation questionnaire. The collected data were then analyzed descriptively and qualitatively. The results showed that the total average of all aspects of the assessment was 81.8 which was included in the "very good" category. Based on this result, it can be concluded that the products developed, namely learning media for "circular motion" material, is suitable for use in the learning process to improve students' higher order thinking skills